(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Chest computed tomography (CT) scan is one of the main modalities to detect COVID-19 infection. Several CT scan findings are the hallmark to rapidly detect suspected COVID-19 infection, therefore timely treatment could be administered. This study aims to describe chest CT scan findings of confirmed COVID-19 patients based on clinical symptom onset patterns. This study is a descriptive study with a retrospective design in confirmed COVID-19 patients. Data regarding characteristics of chest CT scan findings and the patient’s history including clinical symptoms onset were collected. There were 123 subjects in this study. The study data were categorized into modified clinical symptom onset patterns which were early, progressive, peak, absorption, and advanced phases. Most of male (57%) and female (43%) patients that were admitted to the hospital were in absorption phase of the disease with fever, cough, and dyspnea as the most prevalent symptoms. Chest CT scan findings of absorption phase included GGO (ground glass opacity) in 28 patients (76%), crazy paving pattern in 18 patients (49%), consolidation in 22 patients (59%), and fibrosis in 31 patients (84%). Chest CT scan findings of confirmed COVID-19 patients vary depending on the phase of the disease. Risk factors and secondary bacterial infection may contribute to long-term persistence of symptoms.